2021
DOI: 10.3390/s21134415
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk-Derived Cellulose Nanofibers: A Potential Sensor for Water-Soluble Gases

Abstract: Cellulose and its derivatives have evoked much attention in sensor technology as host-matrices for conducting materials because of their versatility, renewability, and biocompatibility. However, only a few studies have dealt with the potential utilization of cellulose as a sensing material without a composite structure. In this study, cellulose nanofibers (CNF) and 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose nanofibers (TOCNF) extracted from rice husks by using ultrasonic-assisted methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Sensors based on these matrices can contribute to monitoring environmental parameters such as humidity, temperature, and pollution levels. Silica's stability and robustness make it suitable for outdoor and harsh environments, enabling longterm monitoring of conditions [58].…”
Section: Sensor Matrix Based On Silica and Silica-cellulose For Vario...mentioning
confidence: 99%
“…Sensors based on these matrices can contribute to monitoring environmental parameters such as humidity, temperature, and pollution levels. Silica's stability and robustness make it suitable for outdoor and harsh environments, enabling longterm monitoring of conditions [58].…”
Section: Sensor Matrix Based On Silica and Silica-cellulose For Vario...mentioning
confidence: 99%
“…Sensors detect and transform physical, chemical, and biological changes in their environment and convert them into analytical signals. Nanocellulose, being a natural nanomaterial, is crucial in the development of new sensors, especially in the context of developing a multidimensional architecture [ 123 , 124 , 125 , 126 ]. Table 6 summarizes the recent developments of nanocellulose-based sensors including electrochemical, optical, colorimetric, fluorescent, and biosensors for the detection of various types of pollutants such as heavy metal ions, water-soluble gases, minerals, and salts.…”
Section: Environmental Applications Of Nanocellulose-based Membranesmentioning
confidence: 99%
“…The porous structure of the modifier and the formation of a compound between copper ions and nitrogen or oxygen-containing groups in DPA-NC may have contributed to the improved electrochemical responsiveness of the modified electrode. Shahi et al [ 125 ] found that the as-prepared CNF and (TEMPO)-oxidized cellulose nanofibers/glycerol (TOCNF/G) sensors demonstrated good gas sensing capability against acetone, ammonia, methane, and hydrogen sulphide after surface modification with TEMPO-mediated oxidation and glycerol. The presence of numerous carboxyl and hydroxyl groups was responsible for the change in ionic conductivity of the sensors in response to gas exposure.…”
Section: Environmental Applications Of Nanocellulose-based Membranesmentioning
confidence: 99%
“…Cellulose-based observable detection materials are organic–inorganic hybrids, which include inorganic–organic free-casting hybrid membranes, electro-spun nanomembranes, and porous hybrid detectors [ 11 , 12 , 13 ]. Cellulose nanofibers derived from rice husks are sensitive to water-soluble gases, such as ammonia and acetone [ 14 ]. Pongpat Sukhavattanakul et al developed a sensor based on bacterial cellulose.…”
Section: Introductionmentioning
confidence: 99%